Spatial distribution shifts of Batocera horsfieldi (Coleoptera: Cerambycidae) and its natural enemies in China under climate change: Implications for biological control - Liang Zhang; Chaokun Yang; Ping Wang; Guanglin Xie; Wenkai Wang (Biological Control)
With the increasing impact of climate change on global ecosystems, the ranges of species are undergoing significant changes. The aim of this study was to assess the potential suitable areas for Batocera horsfieldi (Coleoptera: Cerambycidae) and its natural enemies, Dendrocopos major (Piciformes: Picidae) and Scleroderma guani (Hymenoptera: Bethylidae), in the context of climate change and to explore the feasibility of pre-emptive classical biological control strategies. Predictions by ecological niche modelling combined with current and future bioclimatic factors showed that under future climate scenarios, the suitable areas for B. horsfieldi showed a gradual contraction, while the suitable areas for D. major and S. guani were expanding. In addition, by analyzing the overlap of the suitable areas of the three species, we found that in the future, there is a significant spatial overlap in the suitable distribution areas of natural enemies and pests, which provides new possibilities for biological control. This study provides new perspectives for pre-emptive biological control in the future, emphasizes the importance of screening and obtaining approval for releasing natural enemies after the arrival of the pest, especially in the context of the uncertainty caused by climate change, and provides a scientific basis for the development of integrated prevention and management strategies to deal with the threats posed by B. horsfieldi in the future. The results of this study can help to reduce the agro-ecological risks and promote the development of sustainable agriculture.